Initiating Green Innovation: The Role of Green Transformational Leadership in Corporate Sustainability - Achmada, Aurora Yupita; Hermanto, Bambang; Tresna, Pratami Wulan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
This research aims to explore the MYCL CEO's experiences and perspectives in leading the company, uncover effective leadership strategies towards sustainability, and identify key elements of green transformational leadership style that contribute to achieving environmental and social goals and green innovation performance in his company. The approach was qualitative with a narrative research design and an open-ended interview method. The green transformational leadership style implemented by Adi Reza Nugroho at MYCL positively impacts the company's sustainability by creating a collaborative work environment, achieving environmental and social goals, and improving green innovation performance. Key elements of the company's green transformational leadership style such as support, empathy, openness, and active participation of members can contribute significantly to MYCL's success in achieving its environmental vision and targets. The green transformational leadership of MYCL's CEO, Adi Reza Nugroho, successfully advanced the company's sustainability by developing team competencies, involving members in decision-making, and prioritizing well-being, significantly enhancing environmental goals and green innovation performance. Companies should implement continuous training programs, encourage member engagement, pay attention to member welfare, support collaboration and innovation, and allocate resources for green innovation development